Análise da paisagem e dinâmicas territoriais na bacia hidrográfica do Rio Pardo (RS) - Marques, Ana Flávia (2012)
The watershed river region that makes up the landscape of the Pardo s watershed has characteristics that make it interesting for the application of landscape studies, since, over the centuries, has been undergoing significant transformations physicalenvironmental and socio-territorial resulting in periods of high participation in the economy of Rio Grande do Sul and even the country (XVIII century), followed by a period of stagnation, beginning in the XIX century and extends to the contemporary. At the dawn of the XXI century, this region faces new challenges of environmental and territorial nature, which materialize in the monoculture of rice, the beef cattle industry and the possibility of reopening the port. The research reported here a historical part of which is to present the specific construction of the state territory - construction that is strongly linked to the city that gives its name to watershed studied - Rio Pardo. This approach aims to highlight how the landscape shapes and reacts to development options or how the rationality of capital ownership and is responsible for the production of space. The methodological procedures, based geospatial allowed the qualitative and quantitative analysis of the landscape for the time interval of twenty-two years, which allowed the physical characterization of the river basin (thematic maps of the drainage network, clinografia, and uses hipsometria land for the years 1989, 2000 and 2011) as well as the use of indices for understanding the changes that have shaped the landscape over the years - fragmentation and urbanity. The results indicate that the story and the speed of the process of deforestation associated with the expansion of agriculture, livestock and forestry are considerably modifying the dynamics of the forest or seminatural vegetation remaining in the landscape Pardo s watershed, and such processes are rarely accompanied appropriate conservation strategies. The condition of the remaining natural vegetation Pardo s watershed factors before direct and indirect pressure has to be especially problematic from the standpoint of conservation in the face of evidence of loss of natural landscape. Although the loss of the fragments of natural vegetation in the period from 1989 to 2011, with the replacement of these systems changed by man, is negligible, there is no evidence of the continuation of this trend. With the continued anthropogenic processes the primary question is directed to define the size of the area of natural vegetation in each municipality, inserted within the limits of the Pardo s watershed, which can be converted (changed) for human use, in relation to the condition minimum natural landscape ensured by the existence of functional natural ecosystems. That is, what areas/fragments should be preserved or restored strategically to be reduced pressures on the remaining biodiversity in a given region Pardo s watershed, with the expectation that they are reinstated or provided goods and ecosystem services provided to welfare human. The analyzes in the broad sense, present one of the possible paths to the objectification of subjective relationships established between water, people and landscapes in the Pardo s watershed.